Duration of opioid prescriptions predicts incident nonmedical use of prescription opioids among U.S. veterans receiving medical care. (1st October 2018) - Barry, Declan T.; Marshall, Brandon D.L.; Becker, William C.; Gordon, Adam J.; Crystal, Stephen; Kerns, Robert D.; Gaither, Julie R.; Gordon, Kirsha S.; Justice, Amy C.; Fiellin, David A.; Edelman, E. Jennifer
Highlights: Examined incident nonmedical use of prescription opioids (NMUPO) among veterans. Among veterans prescribed opioids, 15% reported incident NMUPO. Duration of prescription opioid receipt was a risk factor for incident NMUPO. Abstract: Background/Aims: Although nonmedical use of prescription opioids (NMUPO) is a public health problem, few studies have examined the new-onset NMUPO in clinical populations. We estimated NMUPO incidence among veterans in medical care who had received prescription opioid medication and examined correlates of new-onset NMUPO. Design: Prospective cohort study. Setting: Veterans Health Administration primary care and infectious disease clinics in Atlanta, Baltimore, Bronx, Houston, Los Angeles, Manhattan, Pittsburgh, and Washington, DC. Participants: Patients enrolled in the Veterans Aging Cohort Study wave 3 (2005–2007) who received prescription opioids in the previous year and without lifetime NMUPO were followed at waves 4 and 5 (2008–2011). Measurements: Cox proportional hazards regression was used to examine the relationship between duration of prescription opioid receipt and incident NMUPO, adjusting for demographics, alcohol and tobacco use, substance use disorders, psychiatric and medical diagnoses, and medication-related characteristics. Findings: Among eligible participants (n = 815), the median age was 52 (IQR = 47–58) and 498 (59.8%) were Black; 122 (15.0%) reported new-onset NMUPO, for an incidence rate of 5.0 per 100 person-years. In a multivariable Cox model, compared to <30 days, receipt of prescription opioids for 30–180 days (adjusted hazard ratio [AHR] = 1.65 95% CI: 1.06, 2.58) or >180 days (AHR = 1.99, 95% CI: 1.21, 3.29) was associated with incident NMUPO. Conclusions: Duration of prescription opioid receipt is a risk factor for incident NMUPO among veterans receiving medical care. Providers who prescribe opioids should monitor for NMUPO, especially among those with a longer duration of opioid therapy.